The effects of financial planning in supporting international strategy: MMI Murni Sdn. Bhd. - Khadijah Khalid (2017)
MMI Murni Manufarturing Sdn Bhd (MMI Murni) is a Small Medium Enterprise that currently considering to take a further step for their business,which is to go global. Currently, they had succeeded penetrating the China market.However, with the expected increasing demand from other countries,MMI Murni probably will consider to increase its operation especially with regards to the company’s machine capacity. The case study highlighted the importance and effects of financial planning in supporting strategic decision making.In this case ; The Going Global Strategy. From the information gathered from the company and industry, pro-forma financial statements for exporting products are developed.Then,ratios and financial analysis were generated to support quantitative criteria.Other qualitative effects were also found from the issues related. Thus, the importance of pro-forma financial statement obviously supported the recommendation for the company to proceed their international strategy.